BABY GIANT PUBLIC CRYPTOGRAPHY AND GOLDWASSER HOMOMORPHIC CUCKOO HASH SECURED DATA STORAGE IN FOG ENVIRONMENT (CAHIERS MAGELLANES-NS, 2024)
With increasing scale of big data in IoT application, fog computing is a contemporary computing prototype that is broadening Cloud Computing (CC) in connection with the edge of network in the field. Also there is a huge number of storage resources positioned on the edge of the network to manifest a geographical distributed storage as far as fog computing system (FCS) is concerned. It is utilized in storing big data acquired by fog computing nodes and to minimize the costs involved in management for stimulating data to the cloud. However, the fog node storage at the network edge features several types of attacks. Because of this, applying a high security cloud storage service is considered to be a must in today’s scenario. In this work, a method called, Baby Giant Public Cryptography and Goldwasser Homomorphic Cuckoo Hash (BGPC-GHCH) secured data storage with higher data confidentiality rate in fog environment is proposed. The BGPC-GHCHmethod performed key generation, encryption and decryption for increasing the security performance. The proposed method is split into three steps namely, user registration, key generation and encryption/decryption. Initially, in BGPC-GHCH method, user registration is performed where the details of the corresponding users are registered to the fog server. Upon successful completion of user registration for registered user, in the key generation step, fog server generates public key and private key using Baby Giant Step PublicCryptography-based Key Generation. After key pair (i.e., public key and private key) generation, user encrypts the data with public key and transmits the encrypted data to the fog server for secured data storage employing Goldwasser–Micali Homomorphic cryptosystem-based Encryption and Cuckoo Hashing. Cuckoo Hash Function is used by fog server for encrypted user data storage with their hash value. The stored information gets retrieved by user through decryption. This in turn, the data gets stored in more secured manner using BGPC-GHCHmethod. Experimental evaluation is carried out on factors such as encryption time, data confidentiality rate and data integrity with respect to number of data and number of fog users.